Blast Injury Science and Engineering A Guide for Clinicians and Researchers - Bull, Anthony M. J.; Clasper, Jon.; Mahoney, Peter F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This heavily revised second edition provides a comprehensive multi-disciplinary resource on blast injuries. It features detailed information on the basic science, engineering, and medicine associated with blast injuries. Clear, easy to understand descriptions of the basic science are accompanied by case studies of a variety of clinical problems including heterotopic ossification, hearing damage, and traumatic brain injury, enabling the reader to develop a deep understanding of how to appropriately apply the relevant science into their clinical practice. The use of prosthetics, orthotics and osseointegration in rehabilitation is also covered. Blast Injury Science and Engineering: A Guide for Clinicians and Researchers is a valuable interdisciplinary text primarily focused towards clinical medical professionals and trainees seeking to develop a thorough understanding of injury mechanisms, and the latest treatment techniques. In addition, this resource is of use to individuals in other fields whose work centres around blast injury science such as injury mitigation researchers, military scientists and engineers.
Preface: A history of blast injury science and engineering -- Part I Basic science and engineering -- Part II Weapons effects and forensics -- Part III Clinical problems -- Part IV Modelling blast and blast mitigation -- Part V Application and innovation -- Part VI Rehabilitation. .
Keywords: Emergency medicine; Surgery; Emergency Medicine; Surgery; Blast Injuries; Forensic Ballistics; Wounds, Penetrating